2009
DOI: 10.1080/03069880902728598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a school-based counselling service in the UK

Abstract: This research was funded by the NSPCC. We would like to thank the schools that were involved in our research, including the pupils that took part and the school staff and NSPCC Schools Teams who supported the data collection process. We are also grateful to Mary Baginsky for her support and advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
3
26
0
2
Order By: Relevance
“…This is in agreement to Jenkins & Polat (2006) in Fox & Butler (2009);Rembe (2006) and Ribbens-McCarthy (2006). Data also revealed lack of clear school bereavement policies in the selected schools, such as, identification and reporting ones.…”
Section: Discussionsupporting
confidence: 80%
“…This is in agreement to Jenkins & Polat (2006) in Fox & Butler (2009);Rembe (2006) and Ribbens-McCarthy (2006). Data also revealed lack of clear school bereavement policies in the selected schools, such as, identification and reporting ones.…”
Section: Discussionsupporting
confidence: 80%
“…An evidence base confirming the effectiveness of counselling in schools began to accumulate: Fox and Butler (2009) reported on the success of the National Society for Prevention of Cruelty to Children Schools Counselling Project, where before and after TEEN CORE questionnaires from 104 secondary pupils indicated fewer problems and/or less distress; the Place2Be reported the effectiveness of primary-based counselling, showing lower total difficulties, using the data from over 1800 Strengths and Difficulty questionnaires across England and Scotland (Lee, Tiley, & White, 2009). A comprehensive review of 30 audit and evaluation studies by Cooper (2009) found that counselling significantly reduced the psychological distress of young people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the literature is growing and, although there have been many evaluations of counselling with children and young people, evaluative studies of school-based counselling and collaborative approaches are few and far between (Bryan & Griffin, 2010;Fox & Butler, 2009;Gerrard, 2008;Martin & Carey, 2012). One example of an evaluative study is Carter, Evans, Zapata, and Taifa's (2011) report on the implementation of a school-based family counselling model in urban schools in Los Angeles.…”
Section: Review Of the Literaturementioning
confidence: 95%
“…The significance and desirability of these school-community links are often stated within government policy (Bryan & Griffin, 2010;Milbourne, 2005;Ministry of Education, 2007), but application to practice is reportedly variable. Fox and Butler (2009) believed that the provision of school counselling varies significantly from country to country. They described the development of schoolbased counselling and the current push for the integration of services in the United Kingdom, but commented that, in reality, provision of services is very variable.…”
Section: Review Of the Literaturementioning
confidence: 99%